ANALYSIS OF THE IMPACT OF EDUCATION ON SOCIAL MOBILITY AND ECONOMIC WELFARE OF STUDENTS AT ITB AAS I INDONESIA - Dewi Muliasari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to investigate the relationship between the level of student satisfaction with the academic program and their academic achievement at the AAS Indonesia Institute of Business Technology. The research sample consisted of 89 undergraduate students majoring in Accounting who filled out a survey with questions related to their level of satisfaction with various aspects of the academic program. The results of the statistical analysis show that there is a strong and significant relationship between the level of student satisfaction with the academic program and their academic achievement. The higher the level of student satisfaction with the academic program, the higher the academic achievement they achieve. This finding underscores the importance of academic program quality in influencing higher academic achievement. The results of this study have significant implications for education management at ITB AAS Indonesia and similar educational institutions. Improving the quality of academic programs, improving lecturer-student interactions, paying attention to student feedback, and open communication among education stakeholders are steps that can be taken to increase student satisfaction and academic achievement. This research contributes to further understanding of the importance of non-academic factors, such as student satisfaction, in achieving high academic achievement. Follow-up studies can expand this research by considering other factors that may influence this relationship.